Towards traditions - Reyes Tarazona, Roberto (2023)
The article reflects on the inconsistencies that Ricardo Palma had to overcome, essentially the internal ones in his beginnings, and then makes general mention of the contradictions he had to face with the detractors of the community, in his adulthood. The contradictions, in this case, are those of a literary and cultural nature, affecting literary creation and historical research, as essential elements for the writing of traditions. Keywords: romanticism, self-criticism, literary tradition, article of customs, historical novel.